1901 Ariz. Sess. Laws 1251 - (:unkn) unknown (My University, 1901)
Crimes Against the Public Peace, § 381: Prohibited discharge of a gun, pistol, or other firearm in any saloon, dance house, store or other public house or business house in the territory. Also prohibited injury, destruction, or damage of property therein. Violators fined not exceeding three hundred dollars or imprisoned in jail not exceeding six months, or both.
Keywords: DISCHARGE